Abstract TP205: Alzheimer's Disease and Risk of Intracranial Hemorrhage - Zhang, Cenai; Bruce, Samuel; Navi, Babak; Murthy, Santosh; Kamel, Hooman (Stroke (1970), 2025)
Introduction: Alzheimer's Disease (AD), characterized by extracellular deposition of amyloid beta (Aβ) plaques in brain tissue, is often comorbid with cerebral amyloid angiopathy, which carries an elevated risk of intracranial hemorrhage. Furthermore, severe hemorrhagic complications have been observed following the use of new Aβ-targeted immunotherapies for AD. However, there are limited population-based data regarding the risk of intracranial hemorrhage associated with AD. Methods: We performed a retrospective cohort study using inpatient and outpatient claims between 2008-2018 from a nationally representative 5% sample of Medicare beneficiaries ≥65 years of age. The exposure variable was AD, defined by ICD-9-CM code 331.0 and ICD-10-CM code G30.x. The primary outcome was non-traumatic intracranial hemorrhage, defined as a composite of intracerebral hemorrhage (ICH), subarachnoid hemorrhage (SAH), and subdural hemorrhage (SDH) using validated ICD-9-CM and ICD-10-CM diagnosis codes. Secondary outcomes were ICH, SAH, and SDH assessed separately. Cox proportional hazards models were used to determine the associations between AD and outcomes after adjustment for demographics, vascular risk factors, and Charlson comorbidities. Results: Of 2,107,151 patients included, 87,751 (4.1%) had a diagnosis of AD. A total of 14,400 (0.7%) patients were diagnosed with ICH, 6,003 with SAH (0.3%), and 6,650 (0.3%) with SDH. In multivariable Cox proportional hazards analysis, AD was associated with an increased risk of intracranial hemorrhage (adjusted hazard ratio [aHR], 1.54, 95% confidence interval [CI], 1.44-1.65). In adjusted analyses of secondary outcomes, AD was associated with an increased risk of ICH (aHR, 1.35; 95% CI, 1.23-1.48), SAH (aHR, 2.59; 95% CI, 2.26-2.97), and SDH (aHR, 2.05; 95% CI, 1.83-2.30). Conclusions: In a nationally representative cohort of Medicare beneficiaries, AD was associated with an increased risk of spontaneous intracranial hemorrhage. This increased risk was also present for ICH, SAH, and SDH when examined separately.